Synthesis, structure, and corrosion inhibiting properties of REIII 3-thiophenecarboxylate complexes. (15th September 2022) - Vithana, Vidushi P.; Guo, Zhifang; Deacon, Glen B.; Somers, Anthony E.; Junk, Peter C.
Abstract : Two series of Rare Earth (RE) 3-thiophencarboxylate (3TPC) complexes have been synthesized by reactions between a RE salt and Na(3TPC). Based on weight loss measurements and potentiodynamic polarization measurements, the compounds show good corrosion inhibitory properties and act mainly as anodic inhibitors. Abstract : Two series of Rare Earth (RE) 3-thiophencarboxylate (3TPC) complexes have been synthesized by metathesis reactions between a suitable RE salt and Na(3TPC). Single crystal X-ray diffraction determined that light rare earth metals yield nonacoordinate 1D polymeric complexes [Ln(3TPC)3 (H2 O)3 ] n (Ln = La (1a ), Ce (1b ), Pr (1c ), Nd (1d ), Sm (1e ), Gd (1f )) while the heavier elements have a dimeric structure [Ln2 (3TPC)6 (H2 O)4 ]·H2 O (Ln = Dy (2a ), Ho (2b ), Y (2c ), Er (2d ), Lu (2e )) with eight coordinated metal centers. Thermogravimetric analysis (TGA) and microanalysis data of all the compounds except for compound (2e ) are consistent with the composition derived from single-crystal data. However, bulk compound [Lu2 (3TPC)6 (H2 O)4 ]·H2 O (2e ) lost both coordinated and lattice water during the drying process. Based on weight loss measurements, the corrosion inhibitory properties of the synthesized compounds on mild steel show that [Y2 (3TPC)6 (H2 O)4 ]·H2 O (2c ) has the greatest inhibition efficiency (68%). The potentiodynamic polarisation (PP) measurements are generally consistent with immersion test results. However, [Gd(3TPC)3 (H2 O)3 ] n (1f ) exhibited a similar optimum value with an inhibitor efficiency of 70% utilizing this technique. The PP curves show that these compounds act predominantly as anodic inhibitors.